A New Solution for the Director Relaxation Problem in Twisted Nematic Film Based on Wavelet Analysis - Aleksey Kudreyko; Nail Migranov (International Journal of Mathematics and Mathematical Sciences)
The present research considers and explains the application of the Haar wavelets as basis functions in solution of the propagation of perturbations in low-dimensional anisotropic media. The computations of the relaxation problem in the form of traveling waves have shown that the present approach possesses several advantages over regular methods.